PENGARUH PENGETAHUAN ANGGARAN, PARTISIPASI MASYARAKAT DAN TRANSPARANSI KEBIJAKAN PUBLIK TERHADAP FUNGSI DEWAN DALAM PENGAWASAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) - Nuru, Ferdinant; Saerang, David P. E.; Morasa, Jenny (Universitas Sam Ratulangi, 2013)
The purpose of this research is to examine the effect of the knowledge of budget, public participation and public policy transparency towards the local council function within budget control. The results shows that budgets knowledge, public participation and public policy transparency affect the council functions within local budget control. Only transparency of public policies that affect partially the council functions within regional budget control, while the budget knowledge and public participation did not affect the function of the local council within the budget control. The budget knowledge did not affect the council functions within budget control because it poorly supported by the competency level of councilors, while the public participation had no effect because the overall respondents answer can be concluded that public critique and suggestions is less accommodated especially public involvement in the budget advocacy.Key words : The knowledge of budget, public participation, public policy transparency, the local council functions,Â regional budget control.